Self-presentation and identity in the Roman world - Gavrielatos, Andreas (Cambridge Scholars Publishing, 2017)
Questions on identity have been often the main focus of Classical Studies. The starting point of this book is that identity is not a monolithic idea. Instead of exploring what exactly 'identity' is, the contributors here examine how the concept of 'self-presentation' can facilitate our understanding of how individuals present their identities. Moreover, the interpretation of the means and character of this self-presentation itself enables more general conclusions to be drawn. Topics covered in this volume include identities shaped through the self-presentation of authors in Latin literature, a.